Farmers’ attitude towards rapeseed-mustard (Brassica campestris) cultivation in Jammu - KUMAR, RAKESH; SLATHIA, P S; NAIN, M S; PESHIN, RAJINDER; GUPTA, S K; GUPTA, S K; SHARMA, B C (The Indian Journal of Agricultural Sciences, 2020)
The present study was conducted in four sub-tropical blocks of Jammu and Samba and four temperate blocks of Doda and Reasi districts of Jammu division of Jammu and Kashmir during 2016–17. Total of 280 farmers were interviewed for assessing their attitude towards cultivation of rapeseed-mustard (Brassica campestris) crop through a well standardized attitude scale based on Likert technique. The attitude scale consisted of 16 items. Each item was analyzed and explained clearly to draw meaningful inferences. Results showed that 52% of the total sampled farmers had more favourable attitude and 48% had less favourable attitude towards cultivation of rapeseed mustard crop, respectively. The results obtained from t-test show that there is significant difference between attitude score of the farmers of sub-tropical and temperate zone, and output of multiple linear regression model shows that age, level of education, and knowledge level about different production recommendations significantly affected the attitude of respondent farmers towards cultivation of rapeseed mustard crop with a R2 value of 0.153.